Preparation of Pr2NiO4+δ-La0.6Sr0.4CoO3-δ as a high-performance cathode material for SOFC by an impregnation method. (19th February 2023) - Bai, Jinghe; Han, Zhiying; Zhou, Defeng; Zhu, Xiaofei; Wang, Ning; Chen, Ruyi; He, Jing; Yan, Wenfu
Abstract: As a Ruddlesden-Popper (RP) phase solid oxide fuel cell (SOFC) cathode material, Pr2 NiO4+δ (PNO) is a critical challenge for SOFC commercialization due to the lack of oxygen vacancies and insufficient redox reaction (ORR) activity. In this paper, various concentrations of La0.6 Sr0.4 CoO3-δ (LSC) nanoparticles are coated on the surface of PNO by an impregnation method, and the ORR kinetics of PNO is found to be improved by constructing a composite cathode with heterointerfaces. The formation of the heterointerface effectively enhances the transfer of interstitial oxygen in the PNO and the oxygen vacancies in LSC, which can promote the conduction of O 2− in the cathode and thus improves the ORR activity of the material. When the impregnation concentration of LSC reached C LSC = 0.2 mol L −1, the ORR activity can reach the highest level. At 700 °C, the area-specific resistance of PNO-LSC reaches 0.024 Ω cm 2, which is 83.4% lower than that of PNO (0.145 Ω cm 2 ). And the peak power density of PNO-LSC reaches 0.618 W cm −2, which is 1.89 times larger than that of PNO (0.327 W cm −2 ). Therefore, the construction of composite cathodes with heterointerfaces via impregnation provides an alternative strategy for enhancing the ORR activity of the cathode materials in SOFC. Graphical abstract: Image 1 Highlights: Pr2 NiO4+δ -La0.6 Sr0.4 COO3-δ cathode is prepared by impregnation method. The heterointerface promotes the ORR activity of the cathode. Pr2 NiO4+δ -La0.6 Sr0.4 COO3-δ has excellent ORR activity.